Iklan Bibit di YouTube Memengaruhi Pemakaian Aplikasi Bibit - Victor, Nicholas; Yoedtadi, Moehammad Gafar (Prologia, 2024)
Seeds is a mobile application-based online platform for stock and mutual fund investments. Launched simultaneously in 2019 and mainly used by the millennial generation with OJK permission. The capital market is currently being influenced by developments in advertising information technology. This exchange trading system was originally operated manually. Online securities trading systems, on the other hand, are a recent innovation that has emerged because of the growth of information technology. Therefore, the purpose of this research is to find out how advertisements on YouTube are used to attract interest in using the Seeds application. This study used a quantitative method with primary data obtained by distributing questionnaires to each of the 100 respondents. The Independent Sample T Test is the method of analysis, and an analysis program called SPSS Version 25 is used. Based on the findings of this study, Untar Communication Faculty students have very different levels of interest in utilizing the Seeds application in terms of its service features. Regarding issues that have recently had a negative impact on investment, people's interest in using Seeds varies greatly. Users also experience feelings of insecurity because of this problem. As a result, researchers want to see if there are Seed advertisements on YouTube and whether this Seed application will make users feel safe and comfortable. Currently creating an advertisement for the Seeds app on YouTube to encourage students to use it as a place to invest in the digital age. Bibit adalah platform online berbasis aplikasi mobile untuk investasi saham dan reksadana. Diluncurkan secara bersamaan pada tahun 2019 dan terutama digunakan oleh generasi milenial dengan izin OJK. Pasar modal saat ini sedang dipengaruhi oleh perkembangan teknologi informasi periklanan. Sistem perdagangan bursa ini awalnya dioperasikan secara manual. Sistem perdagangan efek online, di sisi lain, merupakan inovasi baru yang muncul sebagai hasil dari pertumbuhan teknologi informasi. Maka dari itu tujuan dari penelitian ini adalah untuk mengetahui iklan di YouTube digunakan untuk menarik minat menggunakan aplikasi Bibit. Penelitian ini menggunakan metode kuantitatif dengan data primer yang diperoleh dengan membagikan kuesioner kepada masing-masing 100 responden. Uji T Sampel Independen adalah metode analisis, dan program analisis yang disebut SPSS Versi 25 digunakan. Berdasarkan temuan penelitian ini, Mahasiswa Fakultas Ilmu Komunikasi Untar memiliki tingkat ketertarikan yang sangat berbeda dalam memanfaatkan aplikasi Bibit dari segi fitur layanannya. Terkait isu-isu yang akhir-akhir ini berdampak negatif terhadap investasi, minat masyarakat untuk menggunakan Bibit sangat bervariasi. Pengguna juga mengalami perasaan tidak aman sebagai akibat dari masalah ini. Alhasil, peneliti ingin melihat apakah ada iklan Bibit di YouTube dan apakah aplikasi Bibit ini akan membuat pengguna merasa aman dan nyaman. Sedang membuat iklan untuk aplikasi Bibit di YouTube untuk mendorong siswa menggunakannya sebagai tempat berinvestasi di era digital.